City as an Image: Xanenetla, Puebla, Mexico, the “Mural City” - Kurjenoja, Anne Kristiina; Ismael Simental, María Emilia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
To build an image and a different, long lasting urban discourse to regenerate a collective identity in the patrimonial heritage district of Xanenetla, Puebla, a group of volunteers of "Colectivo Tomate" proposed in 2010 carry out a project of urban murals in order to detonate a process of empowerment of the public space through collaboration between artists and local residents. In 2011, after the visibility achieved in the social media in Mexico and abroad, Plan for Urban Development of Puebla 2011-2014 included the "Mural City" of Xanenetla as a new cultural attraction in the touristic circuit of the historic city center considering it with potential to benefit the economic development of the historic area. Urban analysis and statistics reveal that the municipal promotion of the tourism industry through urban "gentrification" has put at risk the popular culture of Xanenetla and its local lifestyle. Our research project explores the potential of the local culture of Xanenetla as an alternative resource to achieve a sustainable and culturally sensitive urban development based on the local identity and considering the collaborative experience of Colectivo Tomate and its urban mural project as corresponding starting points.